1986
DOI: 10.1136/jcp.39.9.977
|View full text |Cite
|
Sign up to set email alerts
|

Growth fractions in breast cancers determined in situ with monoclonal antibody Ki-67.

Abstract: The monoclonal antibody Ki-67, prepared by our group,3 reacts with a nuclear antigen present in proliferating cells but absent in quiescent cells. A detailed cell cycle analysis showed that the Ki-67 antigen is expressed throughout the whole cell cycle, making the antibody suitable for the determination of the growth fraction of a benign or malignant human cell subset.4 We recently showed a highly significant correlation between the proportion of Ki-67 positive cells and the histological classification of mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
92
1
6

Year Published

1989
1989
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(113 citation statements)
references
References 12 publications
14
92
1
6
Order By: Relevance
“…The results in patients with leukemia and lymphoma obtained in this study are in accordance with the Ki-67 labeling indices reported in previous investigations (3,5,8,11,13,18,21). However, one should be cautious in comparing the Ki-67 values of different tissue sites, as there might be marked heterogeneity.…”
Section: Discuss I 0 Nsupporting
confidence: 91%
See 1 more Smart Citation
“…The results in patients with leukemia and lymphoma obtained in this study are in accordance with the Ki-67 labeling indices reported in previous investigations (3,5,8,11,13,18,21). However, one should be cautious in comparing the Ki-67 values of different tissue sites, as there might be marked heterogeneity.…”
Section: Discuss I 0 Nsupporting
confidence: 91%
“…A close relationship was demonstrated between Ki-67-positive cells and both 3H-thymidine uptake and the bromodeoxyuridine-labeling index (3 -5,7,16,18-2 1). These Thus far, immunostaining with Ki-67 has been performed primarily on frozen tissue sections (8,10,11,18,21) and cytospin preparations of cell suspensions (3-5,13). Flow cytometric detection of Ki-67-positive cells has been limited because of the nuclear localization of the antigen.…”
Section: Discuss I 0 Nmentioning
confidence: 99%
“…In all breast cancer types, the median proliferation index is considerably lower. 31 Intratumoural heterogeneity provides a hallmark of malignant neoplasm. Therefore, it is an open issue whether subclonal diversity can be reflected reliably by a single biopsy or section from steadily shrinking cancer specimens down to the size of core biopsies in the neoadjuvant setting.…”
Section: Discussionmentioning
confidence: 99%
“…The Ki-67 monoclonal antibody recognises a nuclear antigen present in proliferating cells, but absent in resting cells (Gerdes et al, 1983). Since its original description by Gerdes et al (1983), Ki-67 antibody has been a valuable tool for estimating the proportion of proliferating cells in a number of tumour types (Gerdes et al, 1986;Shepherd et al, 1988). Gerdes' group has recently demonstrated a highly significant correlation between the proportion of Ki-67 positive cells and the histologic classification of lymphomas into high and low grade malignancies (Gerdes et al, 1984).…”
mentioning
confidence: 99%